2023
DOI: 10.3390/electronics12081937
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Algorithm for Calculating the Moisture Content and Time of Forest Fire Maturation of Forest Combustible Materials for Determining Forest Fire Hazards

Abstract: Nowadays, forests play an important role in stabilizing the ecological balance, being one of the most important components of the biosphere. Due to the vital activity of forests, the gas composition of the atmosphere is normalized. Mass forest fires have the opposite effect. They cause irreparable damage to flora and fauna, contribute to the melting of Arctic ice, an increase in the Earth’s temperature, and destabilization of the carbon balance. The purpose of this study is to develop an algorithm for calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Yan Thinking et al [26] concluded that the probability and scale of fire occurrence varied between different forest types. Aleksandrov et al [27] estimated the high incidence period of forest fires from the water content of forest combustibles. Aqil Tariq et al found a significant relationship between the probability of forest fires and the density of the population [28], and Ikhsan et al [29] found a notable link between the forest fire probability and population density in a spatial simulation of forest fire occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Yan Thinking et al [26] concluded that the probability and scale of fire occurrence varied between different forest types. Aleksandrov et al [27] estimated the high incidence period of forest fires from the water content of forest combustibles. Aqil Tariq et al found a significant relationship between the probability of forest fires and the density of the population [28], and Ikhsan et al [29] found a notable link between the forest fire probability and population density in a spatial simulation of forest fire occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…When they occur in windy weather, fires tend to be severe and spread in multiple lines and locations with the changing wind direction. In addition, forest fires often occur in mountainous regions with high altitudes and complex terrain, making it difficult for firefighters and equipment to extinguish the fires [9][10][11][12][13][14]. Forest protection has made great progress, and unmanned aerial vehicles (UAVs) are being used in forest fire detection.…”
Section: Introductionmentioning
confidence: 99%